Pengaruh Pembelajaran Biologi Daring Non-Laboratorium Dimasa Pandemi Covid-19 Terhadap Hasil Belajar Mahasiswa - Fitri Nirwana Hasibuan (Institut Agama Islam Negeri, 2022)
This study aims to examine students ability to understand Biology without using a laboratory during the Covid-19 pandemic with online learning. The method used is descriptive with a questionnaire approach. The results show that learning Biology online without using a laboratory can reduce students enthusiasm and interest in exploring the material obtained and reduce learning satisfaction, curiosity and understanding of scientific studies presented online. Student learning outcomes during the Covid-19 pandemic only reached the affective aspect and did not include psychomotor aspects